Integrating Religious Moderation Values into Islamic Religious Education: A Pedagogical Approach for Primary Schools - Ahmad Ilmi Aslam A’lawi; Nanang Budianto (Journal of Islamic Education Research, 2025)
This study aims to analyze how religious moderation values are systematically integrated into Islamic Religious Education at NU Elementary School 10 Wuluhan, Jember, Indonesia, and to examine the pedagogical strategies, challenges, and institutional supports that shape its implementation. Employing a qualitative case study design, data were collected through semi-structured interviews with teachers and school leaders, classroom observations, and document analysis of lesson plans and school policies. The data were analyzed using thematic analysis to identify recurring patterns related to curricular integration, pedagogical practice, and school culture. The findings indicate that religious moderation is embedded through contextualized curriculum content, dialogical and participatory teaching methods, teacher role modeling, and the reinforcement of Nahdlatul Ulama traditions that emphasize tolerance, balance, inclusivity, and national commitment. Students demonstrate positive engagement when moderation values are connected to local culture, collaborative learning, and real-life moral dilemmas. However, challenges arise from limited curriculum alignment, insufficient professional training, difficulties in assessing value internalization, and socio-cultural influences such as parental conservatism and exposure to radical digital narratives. The originality of this study lies in its in-depth exploration of moderation integration at the primary school level within a Nahdlatul Ulama institutional context. This study contributes theoretically by linking religious moderation with sociocultural and moral development frameworks, and practically by offering a holistic model that integrates curriculum, pedagogy, school culture, and community collaboration to strengthen inclusive religious education.